2019
DOI: 10.1152/japplphysiol.00190.2019
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dynamic left ventricular function, assessed by the strain-volume loop, relate to reverse remodeling after aortic valve replacement

Abstract: Aortic valve replacement (AVR) leads to remodeling of the left ventricle (LV). Adopting a novel technique to examine dynamic LV function, our study explored whether post-AVR changes in dynamic LV function and/or changes in aortic valve characteristics are associated with LV mass regression during follow-up. We retrospectively analyzed 30 participants with severe aortic stenosis who underwent standard transthoracic echocardiographic assessment before AVR [88 (IQR or interquartile range: 22–143) days], post-AVR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Our study shows gives impetus to the thought of intervening early in aortic valve disease by incorporating strain analysis in evaluation of patients for aortic valve replacement. Similar results were observed in many other studies [ 5 , 23 26 ]. Al-Rashid et al found that the global longitudinal strain (GLS) 1 week following TAVR was comparable to that at baseline (−15,9 ± 4.3 vs −16.8 ± 4.1; p = NS) but significantly improved at 3 months following TAVR (−15.9 ± 4.3% vs. −19.5 ± 3.5%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows gives impetus to the thought of intervening early in aortic valve disease by incorporating strain analysis in evaluation of patients for aortic valve replacement. Similar results were observed in many other studies [ 5 , 23 26 ]. Al-Rashid et al found that the global longitudinal strain (GLS) 1 week following TAVR was comparable to that at baseline (−15,9 ± 4.3 vs −16.8 ± 4.1; p = NS) but significantly improved at 3 months following TAVR (−15.9 ± 4.3% vs. −19.5 ± 3.5%; p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that the SVL can detect abnormalities in different cardiac pathologies is in line with earlier studies. Specifically, in previous work we found uncoupling to be higher in both patients with aortic regurgitation and aortic stenosis, whilst changes in uncoupling were also significantly related to cardiac remodeling after aortic valve replacement [11,12]. Pagourelias et al detected a greater uncoupling in potentially stiffer hearts in hypertrophic cardiomyopathy [27].…”
Section: Discussionmentioning
confidence: 69%
“…The strain(ε)-volume loop (SVL) is an echocardiography-based measure that evaluates the dynamic relationship between LV volume and global longitudinal strain across the total cardiac cycle [11][12][13][14][15]. We previously reported that the SVL can successfully detect changes in systolic and diastolic function upon alterations in pre-and afterload, an ability that is also present when using the invasive pressure-volume curve [16,17], whilst the SVL can also distinguish between various cardiac abnormalities [11], and has potential to provide additional predictive value in clinical populations [12,18]. Therefore, this study will evaluate the relation between the SVL characteristics and presence of diastolic dysfunction (DD) in patients suspected of having HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…(28) We found that post-surgery changes in LV strain-volume loop characteristics relate to subsequent cardiac remodeling in patients with aortic stenosis. (17) Therefore, these changes may serve as a proxy of changes in wall stress. Furthermore, we observed different RV loop characteristics in the 'four cornerstones' of the Mitchell classification of sports potentially due to their difference in cardiac structure and function.…”
Section: Introductionmentioning
confidence: 99%